Nitrate poisoning in cattle fed napier grass (pennisetum purpureum) - Seiler, R. J.; Sheikh Omar, Abdul Rahman; Salim, N. (Persatuan Doktor Veterinar Malaysia, 1979)
Nitrate poisoning resulting in the deaths of 5 of a group ofKedah-Kelantan breed cattle is described. The diet consisted solely of Napier grass {Pennisetum purpureurn) fed by a 'cut and carry' system. Levels of nitrate (N0₃-) in the toxic grass aueraged 28.3 mg/g with some samples as high as 44 ug/g while similar grass from 'noll-toxic' areas was 0.7 mg/g .Clinical signs included wealmess, .staggering gait, cyanosis and dyspnoea and necropsy showed the typical chocolate brown blood resulting from seuere methaemoglobinaemia. Treatment with 2 percent methylene blue reversed the clinical signs and prevented further deaths. The reasonsfor the high level of accumulation of nitrate in this Napier grass were not determined and so further inoestigation of nitrate levels in soils and pastures in Malaysia appears warranted